Direct and delayed synergistic effects of extreme temperature, metals and food limitation on tropical reef-associated fish juveniles. (5th November 2022) - Le, Minh-Hoang; Dinh, Khuong V.; Vo, Xuan Thi; Pham, Hung Quoc
Abstract: Tropical fish are fast-growing and high energetic-demand organisms, which can be highly vulnerable to long-lasting effects of heat stress and pollution, particularly under food shortages. We tested this by assessing highly complex direct and delayed interactive effects of an extreme temperature (ET, 32 °C) from a simulated marine heatwave (MHW), copper (Cu, 0, 100, 150 and 175 μg L −1 ) and food availability (limited and saturated food) on early juveniles of a tropical, reef-associated seaperch ( Psammoperca waigiensis ). Cu, ET, and food limitation independently reduced survival and growth, partly explained by reduced feeding. The negative effect of Cu on fish survival was more substantial under ET, particularly under limited food. Delayed interactive effects of Cu, ET, and food limitation were still lethal to fish juveniles during the post-exposure period. These results indicate that reef-associated fish juveniles are highly vulnerable to these dominant stressors, impairing their ecological function as predators in the coral reefs. Graphical abstract: Image 1 Highlights: The vulnerability of reef fish juveniles to multiple stressors is understudied. Effects of Cu, extreme temperature (ET) and food on Psammoperca waigiensis were tested. Cu effects on P. waigiensis were stronger under ET and food limitation. Synergism of Cu, ET, and food limitation prevailed post-exposure period. Ecological functions of reef-associated P. waigiensis can be impaired.